A Study on Brand Consciousness Among Children and its Effect on Family Buying Behaviour in Bangalore City - Vincent, Nithila (Indian Journal of Marketing, 2006)
'Brand', 'Brand Name', 'Brand Equity', 'Brand Loyalty' are forces or terms that affects a business. Product features can be easily copied; therefore brands are considered a marketer's tool for creating product differentiation. Brands differentiate products and represent a promise of value. Brands incite beliefs, evoke emotions, and prompt behaviour. People buy products, but which products they buy and how they make a buying decision have a lot to do with how they feel about the brand. Products are what the company makes, what the customer buys is a brand. Brands work by facilitating and making more effective the consumer's choice process. Brands have a social and emotional value for the users. They have a personality and speak for the user. They enhance the perceived utility and desirability of a product. Brands have the ability to add or subtract the perceived value of a product. Consumers expect to pay lower prices for unbranded products or for those with low brand equities. On the other hand, they are ready to pay a premium for their favorite or socially valued brands.